(untitled) (Journal of Informatics Education and Research, 2025)
Aim: The aim of the present study is to explore Upper Limb Discomfort associated with Smartphone Usage and Internet Addiction across various age groups. Introduction: This study addresses the relationship between smartphone use, internet addiction, and related upper limb discomfort in various ages. As Smartphone become more and more ingrained in daily life, worries about their possible negative impact on both physical and mental health have emerged. These issues are worsened by internet addiction, which is frequently linked to excessive smartphone usage. The preliminary findings show a significant relationship, with differences identified across age groups, between excessive smartphone usage, internet addiction, and upper limb discomfort. Methods of study: Employing a random sampling technique, this study’s cross-sectional design has been implemented in Lucknow city. A total of 180 respondents have been selected for this investigation. Male and female participants were drawn randomly from each of the three age groups (i.e., 18-29; 30-59, and over 60).While responding to the Cornell Hand Discomfort Questionnaire (CHDQ), Internet Addiction Scale (IAS), and Smartphone Addiction Scale-Short Form (SAS-SF) questionnaires. Results & Findings: The study examined upper limb discomfort linked to smartphone use and internet addiction in all age groups by analyzing a sample of 180 respondents. The study’s findings showed that smartphone use, internet addiction, and upper limb discomfort were positively correlated in all age categories. In general, focused interventions are advised to manage musculoskeletal problems brought on by excessive use of Smartphone. Considering the strong positive connection developed between SAS and IAS scores, it appears that those who have higher smartphone rates of dependency are also more likely to be internet addicts. Similarly, a relatively favorable connection between the IAS and CHDQ scores suggests that. The SAS and CHDQ scores showed a significant moderate positive connection, suggesting that people who evaluate their smartphone addiction higher are also more likely to suffer hand pain from using their phones. Higher internet addiction scores are also associated with more hand ache reports. Conclusion: The study highlighted significant associations between upper limb discomfort problematic smartphone usage and internet addiction across different age groups in Lucknow city. Although there were significant changes in the scores of the Smartphone Addiction Scale (SAS) between age groups, there were also notable differences in the way some areas, especially Area F (wrist), interpreted pain. It suggests that those with higher rates of smartphone addiction are also more likely to have internet addictions, given the strong positive correlation that has been established between SAS and IAS scores. The significant moderate positive connection shown between SAS and CHDQ scores suggests that those with higher smartphone addiction scores are also more likely to suffer hand discomfort associated with smartphone use. Similarly, a relatively favorable connection between the IAS and CHDQ scores suggests that individuals with higher internet addiction scores also experience more hand discomfort.